2017
DOI: 10.21577/0103-5053.20170048
|View full text |Cite
|
Sign up to set email alerts
|

DLLME-GC/ECD Method for the Residual Analysis of Parathion-Methyl and its Application in the Study of the UV-Photodegradation Process

Abstract: A new method has been developed to determine trace levels of organophosphorus pesticide parathion-methyl in water samples by using dispersive liquid-liquid microextraction (DLLME), followed by gas chromatograph coupled with electron capture detector (GC/ECD) analysis. The optimized and validated method showed high extraction recovery (101.1%), high enrichment factor (57.3), low limits of detection and quantification, 0.083 and 0.250 μg L -1 , respectively. The established DLLME-GC/ECD method has been successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…143 This insecticide, mainly sprayed on beans, wheat, cotton and fruits, can affect the neurological systems of all living things, including watersheds, humans, and animals. 144 Gopi et al 145 constructed an effective electrochemical sensor based on BiVO 4 as an electrocatalyst for detecting hazardous paraoxon pesticide. The material characterization revealed that the synthesized BiVO 4 had superior conductivity, sufficient oxygen vacancies, and good chemical stability.…”
Section: Metal Oxide-based Electrochemical Sensors For Pesticide Dete...mentioning
confidence: 99%
“…143 This insecticide, mainly sprayed on beans, wheat, cotton and fruits, can affect the neurological systems of all living things, including watersheds, humans, and animals. 144 Gopi et al 145 constructed an effective electrochemical sensor based on BiVO 4 as an electrocatalyst for detecting hazardous paraoxon pesticide. The material characterization revealed that the synthesized BiVO 4 had superior conductivity, sufficient oxygen vacancies, and good chemical stability.…”
Section: Metal Oxide-based Electrochemical Sensors For Pesticide Dete...mentioning
confidence: 99%